Fasilitas “Kids Corner” Pada Perpustakaan Kantor Perwakilan (KPw) Bank Indonesia Provinsi Jawa Barat - Khairan, Khansa Putri; Setiawati, Linda; Khoerunnisa, Lutfi (Universitas Negeri Padang, 2023)
A library is a building that manages various information and provides information services for visitors and users. Where, the facilities in a library building are very important and require special attention. The facilities in the library building of the representative office (KPw) of Bank Indonesia of West Java province include facilities that are quite complete and adequate. One of them is the availability of Kids Corner facilities. The research method used in making this article is a descriptive method with a qualitative approach. With the Kids Corner facility, the aim is that library visitors are expected to continue to grow or increase from various groups, both the general public and students, elementary, junior high and high school students, to children from kindergarten or PAUD.